2021
DOI: 10.1038/s41419-021-04220-7
|View full text |Cite
|
Sign up to set email alerts
|

The polarity protein Par3 coordinates positively self-renewal and negatively invasiveness in glioblastoma

Abstract: Glioblastoma (GBM) is a brain malignancy characterized by invasiveness to the surrounding brain tissue and by stem-like cells, which propagate the tumor and may also regulate invasiveness. During brain development, polarity proteins, such as Par3, regulate asymmetric cell division of neuro-glial progenitors and neurite motility. We, therefore, studied the role of the Par3 protein (encoded by PARD3) in GBM. GBM patient transcriptomic data and patient-derived culture analysis indicated diverse levels of expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…Although PARD3 expression is differentially regulated in human cancers, and PARD3 may function as either an oncogene or tumour suppressor depending on cancer subtype or stage [ 22 ], a recent study showed that in human glioblastoma, PARD3 was enriched in NESTIN-positive stem cells. Similar to our findings, silencing PARD3 was found to lead to a defect in glioma sphere formation in vitro, suggesting that the self-renewal capacity of TICs was lost upon PARD3 silencing [ 41 ]. By single-cell analysis, we showed that in an early established HCC tumour, PARD3 was enriched in cancer cells expressing CD133, the cell surface marker of liver cancer stem cells.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although PARD3 expression is differentially regulated in human cancers, and PARD3 may function as either an oncogene or tumour suppressor depending on cancer subtype or stage [ 22 ], a recent study showed that in human glioblastoma, PARD3 was enriched in NESTIN-positive stem cells. Similar to our findings, silencing PARD3 was found to lead to a defect in glioma sphere formation in vitro, suggesting that the self-renewal capacity of TICs was lost upon PARD3 silencing [ 41 ]. By single-cell analysis, we showed that in an early established HCC tumour, PARD3 was enriched in cancer cells expressing CD133, the cell surface marker of liver cancer stem cells.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our findings, silencing Fig. 7 Mechanisms involved in the regulation of PARD3 on TICs in hepatocarcinogenesis PARD3 was found to lead to a defect in glioma sphere formation in vitro, suggesting that the self-renewal capacity of TICs was lost upon PARD3 silencing [41]. By singlecell analysis, we showed that in an early established HCC tumour, PARD3 was enriched in cancer cells expressing CD133, the cell surface marker of liver cancer stem cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“… 39 Zhou et al 40 reported that loss of Par3 promoted prostatic tumorigenesis. Nevertheless, Dadras et al 41 showed that Par3 participated in homeostatic redox control and limited invasiveness of glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PARD3 was con rmed to have invasion and migration inhibitory effects possibly through regulating cell polarity (Dadras, et al 2021). However, studies have also shown that PARD3 acts as an oncogene in ovarian cancer (Nakamura, et al 2016), prostate cancer (Zhou, et al 2017) and other cancers.…”
Section: Discussionmentioning
confidence: 99%